Recovery of grape waste for the preparation of adsorbents for water treatment: Mercury removal. Issue 3 (June 2020) - Zúñiga-Muro, N.M.; Bonilla-Petriciolet, A.; Mendoza-Castillo, D.I.; Reynel-Ávila, H.E.; Duran-Valle, C.J.; Ghalla, H.; Sellaoui, L.
Highlights: Recovery of grape bagasse biomass to prepare adsorbents was proposed. New adsorbents for mercury removal were synthetized from grape bagasse. Pyrolysis of grape bagasse was analyzed to improve mercury adsorption. Mercury – grape bagasse char interactions were analyzed via DFT. Oxygenated and silicon-based functional groups were involved in mercury adsorption. Abstract: This study has focused on the recovery of grape bagasse biomass to prepare new adsorbents for the removal of mercury from aqueous solutions.